SAT0485 Safety Profile of the IL-1 Receptor Antagonist Kineret® (Anakinra) in a Long-Term Outcome Study in Patients with Severe Cryopyrin-Associated Periodic Syndromes (Caps). (23rd January 2014) - Kullenberg, T.; Löfqvist, M.; Olivecrona, H.; Plass, N.; Kost, B.; Sibley, C.; Goldbach-Mansky, R.
Abstract : Background: Interleukin-1 (IL-1) is a potent mediator of of inflammation. Kineret is a recombinant, non-glycosylated form of the human IL-1 receptor antagonist (IL-1Ra). The safety profile of Kineret is well documented in Rheumatoid Arthritis (RA) with most frequently reported AEs being injection site reactions (ISRs) and headache. Recently anakinra has been used in patients with various autoinflammatory diseases including CAPS and conditions with clinical or in vitro evidence for for IL-1 involvement 1, 2 . Objectives: To characterize long-term safety of Kineret in pediatric and adult patients with severe CAPS (NOMID/CINCA). Methods: A prospective, open-label study including 43 patients (7 adult, 36 pediatric) was conducted at the National Institutes of Health (NIH study 03-AR-0298). Safety was evaluated for up to 5 years, using adverse event (AE) reports, laboratory assessments and vital signs. Results: Age at recruitment was 0.7 - 46.3 years. Total Kineret exposure was 159.8 patient years (128.0 patient years for doses 1-3.5 mg/kg/day, 31.9 patient years for doses ≥3.5 mg/kg/day). There were no deaths or discontinuations due to AEs. 24 serious adverse events (SAEs) were reported in 14 patients. The most common SAEs were infections; with pneumonia (n=3) and gastroenteritis (n=2) being the most frequent. Overall, the most commonly reported AEs were events that also may be symptoms of CAPS (headache, arthralgia, pyrexia, rash) and upper respiratory tract infections. In total 7.7 AEs were reported/patient year; 86.0% were mild. The AE reporting frequency was highest during the first 6 months. Ten patients reported 17 ISRs, 13 were mild, 4 moderate and none required temporary or permanent discontinuation. The majority of ISRs occurred during the first month. The frequency of ISRs in this study was similar to that seen in placebo-treated patients in RA studies. There were 273 infections reported. Upper respiratory tract infections and nasopharyngitis were most common. Kineret was temporarily stopped during one infection. In 5 patients the Kineret dose was increased due to concomitant disease flares, in all other cases Kineret treatment was continued unchanged. Dose (1-3.5 mg/kg/day vs. ≥3.5 mg/kg/day), gender or presence of NLRP3 mutation did not affect the AE reporting frequency. AE profiles in pediatric and adult patients were similar, with the exception of infections and related symptoms being more frequent in patients <2 years. Conclusions: Kineret is well tolerated when administered for up to 5 years to patients with severe CAPS. There is no indication of increasing frequency of AEs when higher doses of Kineret are used. No new clinically relevant AEs emerged compared to the established safety profile of Kineret. The frequency of treatment induced ISRs in severe CAPS is low. There were no permanent discontinuations of Kineret treatment due to AEs. Continued Kineret treatment during infections were well tolerated and could be considered in severe CAPS to avoid flares. References: Dinarello Charles A. et al. Nat Rev Drug Discov 2012, 11: 633-652 Sibley Cailin H. et al. Arthritis Rheum 2012, 64: 2375–2386 Disclosure of Interest: T. Kullenberg Employee of: Swedish Orphan Biovitrum AB, M. Löfqvist Employee of: Swedish Orphan Biovitrum AB, H. Olivecrona Employee of: Swedish Orphan Biovitrum AB, N. Plass: None Declared, B. Kost: None Declared, C. Sibley: None Declared, R. Goldbach-Mansky Grant/research support from: Swedish Orphan Biovitrum AB, Regeneron, and Novartis